PEMBERIAN PANGAN YANG DIFORTIFIKASI ZAT MULTI GIZI MIKRO DAN PENGARUHNYA TERHADAP STATUS ANEMIA DAN PERTAMBAHAN BERAT BADAN IBU HAMIL - V Prihananto; Rimbawan Rimbawan; Made Astawan; Ahmad Sulaeman (Media Gizi dan Keluarga, 2006)
ABSTRACT. The objetive of this study was to evaluate the effect offeeding with multimicronutrients fortified foods on anemia status and weight gain ofpregnan womrql. This study was carried out in three sub-districts in Bogor, i. e.: Leuwiliang, Leuwisadeng and Ciampea. A double blind randomized control trial was assigned on this study. About 210 pregnant women from these sub-districts were selected for this study and devided into 2groups, (1) 70 pregnant women received fortified foods with multi-micronutrients i.e. iron, iodine, zinc, folic acid, vitamin C, and vitamin A, and (2) 70 pregnant mothers received nonfortifiedfoods, each for 6 mounths. Product chosen as intervention carrier consisted of vermicelli, milk, and biscuit. Distribution ofproducts were carried out every week to thetarget pregnant women. The results of the study showed: (a) intervention could reduce prevalence ofanemia as much as 28% compared with placebo (b) Intervention affected the micronutrients consumption andfulfilled: iron 55,5% RDA, vitamin A 65% RDA, vitamin C 126% RDA, folat 15,3% RDA, zinc 26,7% RDA, iodium 26,3%, (c) intervention didn'tinfluence weight gain during pregnancy.